Parallel behavior composition for manufacturing - Felli, Paolo; Logan, Brian; Sardina, Sebastian (2016)
A key problem in the manufacture of highlycustomized products is the synthesis of controllers able to manufacture any instance of a given product type on a given production or assembly line. In this paper, we extend classical AI behavior composition to manufacturing settings. We first introduce a novel solution concept for manufacturing composition, target production processes, that are able to manufacture multiple instances of a product simultaneously in a given production plant. We then propose a technique for synthesizing the largest target production process, together with an associated controller for the machines in the plant.